Prevalence of Listeria monocytogenes in frozen burger patties in Malaysia - Wong, Woan Chwen; Pui, Chai Fung; Robin, Tunung; Cheah, Yoke Kqueen; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
A total of 112 burger patties (35 beef burger patties, 39 chicken burger patties and 38 fish burger patties) which are commercially available at retail level were investigated for the presence and number of Listeria monocytogenes. These samples were analyzed using MPN-PCR method and conventional culturing methods. L. monocytogenes was detected in 33.3% of chicken burger patties, 22.9%of beef patties, and 10.5% of fish patty samples. From all contaminated raw burger patties, the estimated count of L. monocytogenes was ranged from 3 to 75 MPN/g. The results suggest that burger act as a potential source of listeriosis if the contaminated burger patty is consumed without adequate cooking. The risk associated with consumption of these samples was found to be high particularly for processed food at retail level in Malaysia. Therefore, food manufacturers play an importantrole in monitoring the manufacturing process and conduct a periodical surveillance on microbiological quality assessment on the processing plants. Besides, there is a need to increase awareness ofconsumers and food handlers to practice proper cooking of the burger patties before the point of consumption, to reduce the risk of listeria infection.